Comparative Analysis of Different Biophysical Techniques for Exosome Characterization - Yu, Xiaojuan; Wang, Zhaoxing; Zhang, Ruifeng; Guo, Wenli; Chang, Qing; Chu, Wendan; Zeng, Chengshi; Wang, Lan; Yu, Chuanfei; Li, Wenqi (浪淘沙预印本平台, 2025)
Exosomes, as key mediators of intercellular communication, have demonstrated great potential in drug delivery. However, their accurate characterization remains challenging due to their complex physical properties. This study purified exosomes from milk and human urine using ultracentrifugation and the EXODUS systems and systematically compared several biophysical techniques to characterize them, including dynamic light scattering (DLS), nanoparticle tracking analysis (NTA), NanoCoulter technology, and analytical ultracentrifugation (AUC). DLS was found to be suitable for the rapid preliminary assessment of homogeneous samples but it is sensitive to large particles and has limited repeatability. NTA provides better resolution of particle size distribution and dynamic changes. NanoCoulter offers absolute particle concentration but is constrained by its detection range, and AUC demonstrates unique advantages in assessing sample purity using sedimentation behavior and UV absorption. The study findings suggest that a single technique is insufficient for comprehensive exosome characterization. Integrating multiple methods for orthogonal validation may help to establish a more reliable exosome characterization system.